A new monopole antenna in the form of double dollar-symbol for WLAN (5.1- 6 GHz) applications - Sabbar, Nisrin (2018)
In this paper, we present a new monopole antenna design for WLAN (5.1-6 GHz) application. The proposed antenna fed by a microstrip and the radiating element is in the form of a double dolar-symbole. The antenna designed is printed on a partial ground plane, and the resulting antenna has been found to possess a compact size of 20 mm × 20 mm, and covers specific bands from the frequency spectra. A parametrical study is performed to optimize the geometry of the antenna structure and a comparison study also will be presented for different kind of ground plane material. The designed antenna structure is simulated using the High Frequency Structural Simulator (HFSS)